Transforming Competitive MSMEs through Community Engagement: Integrating Digital Technology and Local Wisdom - Suherlan; Lili Fadli Muhamad; Valentino Aris (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
This study aims to examine the transformation of competitive Micro, Small, and Medium Enterprises (MSMEs) through community engagement, with a particular emphasis on the integration of digital technology and local wisdom. The research employs a literature review method using a qualitative approach and descriptive analysis of 29 selected scientific articles published between 2021 and 2025. Data sources were obtained from Google Scholar and various credible websites relevant to community engagement and MSME development. The findings indicate that community engagement plays a strategic role as an empowerment instrument capable of bridging the gap between academic innovation and the practical needs of MSMEs. The integration of digital technology has been proven to enhance business efficiency and market expansion, while local wisdom functions as a source of differentiation and product identity that strengthens competitiveness. However, the success of MSME transformation is highly dependent on the sustainability of mentoring, the suitability of technology to the capacity of business actors, and sensitivity to the socio-cultural context. This study is expected to contribute to the academic literature on community engagement and serve as a conceptual foundation for policy formulation and sustainable MSME empowerment practices.